Gayspeak and Gay Subjects in Audiovisual Translation: Strategies in Italian Dubbing - Ranzato, Irene (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
The purpose of this article is to analyse the fictional language of homosexuals as portrayed on the screen, as well as the way in which Italian translators and dubbing adapters have dealt with gayspeak. It means to explore whether the words of the gay lexicon in the English and the Italian languages cover similar semantic areas and whether any lack of balance between the two languages in this particular field may create problems for the translator. On the other hand, various examples from dubbed films and TV programmes will help to investigate whether some of the features of gayspeak are substantially altered in the Italian adaptations and whether these modifications are due to constraints determined by the vocabulary used to define the idiolect of this speech community or, rather, to overt and covert constraints imposed by a culture, the Italian, which has opened up to homosexual themes much more slowly than the Anglosaxon world.